A consecutive‐competitive reaction system for assessing homogeneous and heterogeneous liquid–liquid mixing efficiency. Issue 11 (13th July 2022) - Zhang, Yi‐Dong; Wang, Ze‐Xin; Zhang, Liang‐Liang; Sun, Bao‐Chang; Chu, Guang‐Wen; Chen, Jian‐Feng
Abstract: Here, the consecutive‐competitive reaction system about aspirin and sodium hydroxide was proposed as a unified chemical probe to characterize the homogenous and heterogeneous liquid–liquid mixing. The kinetics of the reaction system was clearly studied. Then the mixing efficiencies were assessed in a standard stirred tank with this chemical probe and the obtained segregation index ( X S ) could well characterize the mixing performance. Based on the incorporation model, the estimation formula of micromixing time was established as t m = 13.956 ν / ε 0.5 . The chemical probe could show the influence of stirring intensity, interphase resistance, and two‐phase ratio on the mixing efficiency sensitively when it was extended to heterogeneous mixing. Using this chemical probe, we found the mixing efficiencies of homogeneous and heterogeneous process tended to be the same at sufficiently high stirring intensity. The reason for this phenomenon was unveiled by investigating the dispersed phase size and calculating mass transfer time.